2022
DOI: 10.1093/ibd/izac124
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Care for Black and Hispanic Inflammatory Bowel Disease Patients

Abstract: Research on the care of inflammatory bowel disease (IBD) patients has been primarily in populations of European ancestry. However, the incidence of IBD, which comprises Crohn’s disease and ulcerative colitis, is increasing in different populations around the world. In this comprehensive review, we examine the epidemiology, clinical presentations, disease phenotypes, treatment outcomes, social determinants of health, and genetic and environmental factors in the pathogenesis of IBD in Black and Hispanic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Barriers to care, such as lengthy wait times and inaccessibility to a dietician or IBD specialist, are even more pronounced in patients of minority backgrounds, which can further exaggerate disparities and lead to delays in diagnosis and treatment. (30) LLMs may empower these patients with knowledge regarding their disease, giving them a tool which helps them proactively engage with their healthcare providers. LLMs may also prove beneficial to patients who have language discordance with their healthcare providers, given disparities in healthcare outcomes based on language preference have been previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to care, such as lengthy wait times and inaccessibility to a dietician or IBD specialist, are even more pronounced in patients of minority backgrounds, which can further exaggerate disparities and lead to delays in diagnosis and treatment. (30) LLMs may empower these patients with knowledge regarding their disease, giving them a tool which helps them proactively engage with their healthcare providers. LLMs may also prove beneficial to patients who have language discordance with their healthcare providers, given disparities in healthcare outcomes based on language preference have been previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…Though IBD has historically been associated with patients of European ancestry, recent studies have shown that the incidence of IBD is increasing in other populations as well (20). Studies have also shown a difference in clinical presentation between races, particularly between Hispanic and non-Hispanic White patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 Access to care, disease assessment, clinical trial enrollment, and evaluation of environmental factors have all been prioritized for future research in this population. 12…”
Section: Background: Racial Inequities In Inflammatory Bowel Disease ...mentioning
confidence: 99%
“…11 Access to care, disease assessment, clinical trial enrollment, and evaluation of environmental factors have all been prioritized for future research in this population. 12 It is estimated that a large percentage of patients with IBD will require surgery in their lifetime; 15.2% of patients with ulcerative colitis and 47% of patients with Crohn's disease will require intestinal surgery within 10 years of diagnosis. 13,14 Following IBD surgery, NHB patients have been associated with more complicated postoperative recoveries as illustrated by longer lengths of stay, higher readmission rates, and higher odds of death or serious morbidity.…”
Section: Background: Racial Inequities In Inflammatory Bowel Disease ...mentioning
confidence: 99%